Advances in the microbiological diagnosis of herpetic retinitis - Gueudry, Julie; Bodaghi, Bahram (Frontiers in Ophthalmology, 2022)
Viral retinitis associated with herpesvirus is one of the most severe forms of uveitis and is a potentially sight-threatening ophthalmologic disease. The prognosis is poor and a rapid and aggressive management is necessary to improve the visual and sometimes vital prognosis of these patients. The treatments used are not without side effects, while many differential diagnoses exist, such as toxoplasmic retinochoroiditis, syphilitic retinitis, endogenous endophthalmitis and intraocular lymphoma. Causatives viruses are herpes simplex virus, varicella-zoster virus, and cytomegalovirus, which require rapid detection in ocular fluid, mainly aqueous humor. However, only a small amount of intraocular fluid is available for analysis. Advances in microbiological diagnostic techniques therefore were key factors in improving the management of these diseases. Historically, the diagnosis was based on immunological tests but more recently advances in molecular biology, in particular polymerase chain reaction, have played a crucial role to obtain a reliable and rapid diagnosis of viral retinitis associated with herpesvirus, as discussed in this review.